A Single‐Step Hydrothermal Route to 3D Hierarchical Cu2O/CuO/rGO Nanosheets as High‐Performance Anode of Lithium‐Ion Batteries. Issue 5 (11th December 2017) - Wu, Songhao; Fu, Gaoliang; Lv, Weiqiang; Wei, Jiake; Chen, Wenjin; Yi, Huqiang; Gu, Meng; Bai, Xuedong; Zhu, Liang; Tan, Chao; Liang, Yachun; Zhu, Gaolong; et al.
Abstract: As anodes of Li‐ion batteries, copper oxides (CuO) have a high theoretical specific capacity (674 mA h g −1 ) but own poor cyclic stability owing to the large volume expansion and low conductivity in charges/discharges. Incorporating reduced graphene oxide (rGO) into CuO anodes with conventional methods fails to build robust interaction between rGO and CuO to efficiently improve the overall anode performance. Here, Cu2 O/CuO/reduced graphene oxides (Cu2 O/CuO/rGO) with a 3D hierarchical nanostructure are synthesized with a facile, single‐step hydrothermal method. The Cu2 O/CuO/rGO anode exhibits remarkable cyclic and high‐rate performances, and particularly the anode with 25 wt% rGO owns the best performance among all samples, delivering a record capacity of 550 mA h g −1 at 0.5 C after 100 cycles. The pronounced performances are attributed to the highly efficient charge transfer in CuO nanosheets encapsulated in rGO network and the mitigated volume expansion of the anode owing to its robust 3D hierarchical nanostructure. Abstract : CuO with 25 wt% reduced graphene oxide (rGO) owns the best cycling capability and shows no obvious capacity loss after 100 cycles. The high specific surface area improves the loading capacity of Li ions and the reduced size of CuO favors lithium‐ion transport. The 3D hierarchical rGO reduces volume expansion during cycling.